Tuning of speed-governing system for Kalayaan Pumped Storage Power Plant - Calibjo, Cirilo C. (1995)
Changes in system frequency are caused by any imbalance between load and generation. To control these, a speed governor is usually provided. The change in frequency maybe either stable or unstable depending on the values of the parameters of the plant and governor. This paper describes a simple analytical procedure of tuning electro-hydraulic P.I.D. governors for the units of Kalayaan Pumped Storage Power Plant. Mathematical analysis is carried out using MATLAB simulation software, while validation through time simulation is performed using Power System Simulator/Engineering (PSS/E). Optimum gain settings were found both during isolated and grid operations. Although actual plant testing was not possible, the result of the study is seen as an improvement from the usual trial-and-error approach which is currently being practiced.